Plan de desarrollo local del partido de La Plata, casco urbano y delegaciones (Municipalidad, 1999)
Contenido: - V.1: Casco Norte - V.2: Casco Sur Este. - V.3: Abasto. - V.4: Arturo Seguí. - V.5: City Bell. - V.6: Etcheverry. - V.7: El Peligro. - V.8: Gonnet. - V.9: Hernández / Gorina. - V.10: Los Hornos. - V.11: Melchor Romero. - V.12: San Carlos. - V.13: Olmos. - V.14: Ringuelet. - V.15: San Lorenzo. - V.16: Tolosa. - V.17: Villa Elisa. - V.18: Villa Elvira.